Irresponsibility for any damage of the surrounding residence - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding irresponsibility for any damage of the surrounding residence of BRAC University new campus project.